Carpal bone replacement using personalized 3D printed tantalum prosthesis - Zhang, Changgui; Chen, Hao; Fan, Huaquan; Xiong, Ran; He, Rui; Huang, Chengjun; Peng, Yang; Yang, Pengfei; Chen, Guangxing; Wang, Fuyou; Yang, Liu (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Scaphoid and lunate fractures have a relatively high incidence rate.Traditional carpectomy and carpal arthrodesis in the treatment of carpal osteonecrosis will lead to many complications. Three-dimensional (3D) printed tantalum has good biocompatibility and can be designed to match the patient's personalized anatomical carpal structure. This study aims to investigate the carpal function and prosthesisrelated conditions after carpal bone replacement using 3D printed tantalum prosthesis.Methods: Seven patients with osteonecrosis of the carpus in our Center from July 2020 to January 2022 received carpal bone replacement using 3D printed tantalum prosthesis. The Disability of the Arm, Shoulder and Hand (DASH) score and patient satisfaction, as well as the Mayo Wrist Scores (Cooney method, modified Green and O'Brien wrist score) were used to evaluate the preoperative and postoperative wrist function in patients. The Visual Analog Scale (VAS) pain scores were also recorded before and after surgery. The angles of flexion, dorsiflexion, ulnar deviation, and radial deviation were measured using an arthrometer. Grip strength and pinch strength of the operated hand after carpal bone replacement and the contralateral healthy carpus were measured using a dynamometer. Radiographs were taken to confirm the condition and complications of the tantalum prosthesis.Results: All 7 patients were followed for 19.6±2.7 months. At the last follow-up, the grip strength of the operated wrist joint after carpal bone replacement was 33.4±2.3 kg, the pinch strength was 8.9±0.7 kg, the flexion was 54.6±0.8°, the dorsiflexion was 54.7±1.7°, the ulnar deviation was 34.6±1.9°, and the radial deviation was 25.9±0.8°, all of which showed no statistically significant difference with the contralateral healthy carpus (P>0.05). There were significant differences in the VAS, DASH, and MAYO scores between the preoperative and the last follow-up (P<0.01). Patients had reduced postoperative pain, improved wrist function and range of motion (ROM), and the tantalum prostheses were stable.The 3D printed tantalum brings us new hope, not only for hip or knee replacement, but also for joint replacement of other complex anatomical structures, and patients with other irregular bone defects such as bone tumor and deformity, which could realize personalized treatment and precise medicine.